DILEMMA BETWEEN THE USE OF AUGMENTED REALITY AND THE INFLUENCE OF WORK IN LEARNING - Ahmad Sahar Syamsudin; Charirotul Chusna (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2022)
Abstract This article aims to analyze the problems that often arise in society regarding the use of Augmented Reality technology and gadgets. The problem is the feeling of dilemma when using gadgets as learning media to activate the Augmented Reality feature as a new innovation in learning. The method used is descriptive qualitative. The data is taken from the relevant literacy and then described and analyzed related to the contents of the use of Augmented Reality technology and the use of gadgets in learning. The results obtained are positive and negative impacts caused by the use of gadgets and the application of Augmented Reality in learning. Therefore, if humans can think broadly and futuristic and are aware of the changing times, it is hoped that humans can blend in and interact with technology. So that it can eliminate or minimize negative impacts and can benefit from positive impacts. For this reason, it is necessary to have an awareness, commitment, and certain regulations in the use of gadgets and Augmented Reality. Keywords: Device, Augmented Reality, Learning, Dilemma. Abstrak Artikel ini bertujuan untuk menganalisis permasalahan yang kerap timbul di masyarakat terkait penggunaan teknologi Augmented Reality dan gawai. Permasalahan tersebut ialah perasaan dilema saat menggunakan gawai sebagai media pembelajaran untuk mengaktifkan fitur Augmented Reality sebagai inovasi baru dalam pebelajaran. Metode yang dipakai ialah kualitatif deskriptif. Data diambil dari literasi yang relevan kemudian di deskripsi dan dianalisis terkait isi tentang pemanfaatan teknologi Augmented Reality dan penggunaan gawai dalam pembelajaran. Hasil yang diperoleh ialah adanya dampak positif sekaligus negatif yang ditimbulkan dalam penggunaan gawai dan penerapan Augmented Reality dalam pembelajran. Oleh karena itu, bila manusia dapat berfikir secara luas dan futuristik serta menyadari terhadap perubahan jaman maka diharapkan manusia dapat berbaur dan berinteraksi dengan teknologi. Sehingga dapat menghilangkan atau meminimalisir dampak negatif dan dapat meraih manfaat dari dampak positif. Untuk itu perlu adanya suatu kesadaran, komitmen, dan peraturantertentu dalam pemanfaatan gawai dan Augmented Reality. Kata Kunci: Gawai, Augmented Reality, Pembelajaran, Dilema.